Diagnostic Workup for Disorders of Bone and Mineral Metabolism in Patients with Chronic Kidney Disease in the Era of KDIGO Guidelines - Luigi Francesco Morrone; Domenico Russo; Biagio Di Iorio (International Journal of Nephrology)
KDIGO (Kidney Disease: Improving Global Outcomes) is an international nonprofit organization devoted to “improve the care and outcomes of kidney disease patients worldwide through promoting coordination, collaboration, and integration of initiatives to develop and implement clinical practice guidelines.” The mineral and bone disorder (MBD) in patients with chronic kidney disease (CKD) has been the first area of interest of KDIGO international initiative. KDIGO guidelines on CKD-MBD were published in 2009 with the intent to modify the previous KDOQI guidelines that had failed to consistently change the global outcome of CKD patients. After the publication of KDOQI guidelines for bone metabolism and disease in 2003, a large number of observational data emerged in literature linking disordered mineral metabolism with adverse clinical outcomes. Notwithstanding this large body of observational data, a paucity of evidence from high-quality clinical trials was available for the development of KDIGO guidelines. Herein, a summary will be provided of the most important findings of KDIGO guidelines regarding the diagnostic workup and clinical monitoring of CKD-MBD patients.